2020
DOI: 10.3390/ijms21197359
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Gut Microbiota and Colon Diseases with a Focus on Adenomatous Colon Polyps

Abstract: It is known and accepted that the gut microbiota composition of an organism has an impact on its health. Many studies deal with this topic, the majority discussing gastrointestinal health. Adenomatous colon polyps have a high prevalence as colon cancer precursors, but in many cases, they are hard to diagnose in their early stages. Gut microbiota composition correlated with the presence of adenomatous colon polyps may be a noninvasive and efficient tool for diagnosis with a high impact on human wellbeing and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 159 publications
0
8
1
Order By: Relevance
“…In this study, the richness of gut microbiota in the normal colorectal mucosa and polyps was significantly higher than in faeces, which was inconsistent with the results of some studies ( Pop et al., 2020 ; Zhou et al., 2021 ). Accumulating studies have explored the gut microbiota in individuals and identified a wide range of different bacterial groups associated with carcinogenesis, including Bacteroides, Fusobacterium , Escherichia and Streptococcus ( Mangifesta et al., 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the richness of gut microbiota in the normal colorectal mucosa and polyps was significantly higher than in faeces, which was inconsistent with the results of some studies ( Pop et al., 2020 ; Zhou et al., 2021 ). Accumulating studies have explored the gut microbiota in individuals and identified a wide range of different bacterial groups associated with carcinogenesis, including Bacteroides, Fusobacterium , Escherichia and Streptococcus ( Mangifesta et al., 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…It is not surprising that the intestinal microbiome, the barrier that mediates between our environment and our genes, has been seen as a main cause of many diseases, such as colon cancer, diabetes, obesity, and the development of autoimmune diseases ( Imhann et al, 2018 ; Sethi et al, 2018 ; Olsson et al, 2020 ). Direct or indirect interventions to regulate disease progression by affecting the intestinal microbiome, through strategies such as faecal transplantation, drugs and diet, have become a hot new topic of research ( Bauer et al, 2018 ; Huang F. et al, 2019 ; Pop et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ieni A, Branca G, Parisi A, (2015) in patients over 72 years of age, a distinctive morphological sign of malignancy is associated with an increase in neutrophil infiltration, although the true mechanism of this process is also unclear [20].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%